English Loanwords in Tamil: Fix Illicit Consonant Clusters - Pushpa Rani Subramani Selvan (Yayasan Ilomata, 2022)
Loanword adaptation has long proved field as an intriguing object of study. Loanword borrowing often takes place within languages to fill the glossary of the new terminology. The direction of borrowing is primarily linked to the sociolinguistic status of a language in a community. In the scenario of Malaysia, Malay as a national language and English as a global language plays an essential role in the process of loanword adaptation, technologically, culturally and politically. English and Tamil languages have two disparate grammatical elements. Some grammatical rules accepted in English is illicit in Tamil. In particular, consonant clusters in the English language are prohibited in Tamil. Therefore, words borrowed from English into Tamil are subject to choose one of these two contradictory rules, whether adapt the consonant cluster in its authenticity or repairing to satisfy the grammar of the recipient language. The study results show that some borrowed English loan words obey Tamil grammar, while others violate the rules. This raises questions about the adaptation process's possible representational versus phonetic underpinnings. This paper examines the phonetic adaptation of English loanwords in Tamil adaptation, focusing primarily on the process of vowel epenthesis. It finds that the place features of the epenthetic vowel overcome illegal consonant clusters. The paper concludes that the language-specific phonological phenomena are central to this process. Data for this research were obtained from Tamil short stories (2000-2016). Many studies have been conducted to examine loanword adaptation in Malaysian Tamil. However, this study explores the repairing process of phonetic variations in the adapted words.